Rare Booms and Disasters in a Multisector Endowment Economy - Tsai, Jerry; Wachter, Jessica A. (Review of Financial Studies, 2016)
Why do value stocks have higher average returns than growth stocks, despite having lower risk? Why do these stocks exhibit positive abnormal performance, while growth stocks exhibit negative abnormal performance? This paper offers a rare-event-based explanation that can also account for the high equity premium and volatility of the aggregate market. The model explains other puzzling aspects of the data, such as joint patterns in time-series predictablity of aggregate market and value and growth returns, long periods in which growth outperforms value, and the association between positive skewness and low realized returns.